Write a Scientific Paper (WASP): Which journal to target and why?. (February 2019) - Cuschieri, Sarah; Vassallo, Josanne
Abstract: Publishing scholarly work is a requisite in academia. Identifying a suitable journal for a particular paper can be difficult. Authors need to initially establish whether they want to publish in a subscription-based or an open access journal, which requires a clear understanding of the pros and cons of both options as well as issues relating to copyright licences. Establishing specific journal selection criteria ranging from whether to publish in a general or a specialised journal to the publication frequency of the journal is essential. A number of web-based tools are available that can facilitate this selection process.